PENGARUH JUMLAH WAJIB PAJAK ORANG PRIBADI DAN BADAN TERHADAP PENERIMAAN PAJAK INDONESIA DENGAN KEPATUHAN PELAPORAN PAJAK SEBAGAI VARIABEL PEMODERASI - Indraswono, Cahyo (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2019)
ABSTRACTThis study aims to examine the effect of the number of taxpayers on tax revenue for Indonesia's economic growth with taxpayer compliance as a moderating variable. One indicator in state revenue is the number of taxpayers contained in a country that is expected to be able to contribute to the state revenue. In a country with high taxpayer compliance, it is expected to be able to improve the relationship between the number of taxpayers and tax revenues for Indonesia's economic growth. This research was conducted at the Ministry of Finance of the Directorate General of Tax of the Republic of Indonesia (DGT RI). The Directorate General of Taxation as an entity that has authorization in tax regulation is expected to be able to enforce the law, especially in the field of taxation in order to increase state revenues as part of Indonesia's economic growth. Compliance with taxpayers on the taxation law is allegedly able to increase the influence between the number of taxpayers and tax revenue for economic growth. The hypotheses compiled in this study are: (H1) the number of taxpayers has a positive effect on tax revenue; (H2) that information technology has a positive effect on taxpayer satisfaction; (H3) satisfaction of taxpayers has a positive effect on tax compliance; (H4) law enforcement has a positive effect on tax compliance; (H5) tax compliance has a positive effect on the relationship between the number of taxpayers and tax revenue; and (H6) tax revenue has a positive effect on economic growth. The results of this study indicate that H1, H2, H5 and H6 are supported while H3 and H4 are not supported. Testing of the relationships between variables in this study uses secondary data contained in the annual report of the Directorate General of Tax of the Republic of Indonesia (DGT RI) in 2012-2015 by using multiple regression analysis. Research data used in covering data of all taxpayers located throughout Indonesia, including data of individual taxpayers, treasurers, and corporate taxpayers. Keywords: number of taxpayers; tax revenue; economic growth; taxpayer compliance ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh jumlah wajib pajak orang pribadi dan badan terhadap penerimaan pajak untuk pertumbuhan ekonomi Indonesia dengan kepatuhan pelaporan pajak sebagai variabel pemoderasi. Salah satu indikator dalam penerimaan negara adalah jumlah wajib pajak yang terdapat dalam suatu negara yang diharapkan mampu memberikan kontribusi bagi penerimaan negara. Dalam suatu negara dengan kepatuhan wajib pajak yang tinggi diharapkan mampu meningkatkan hubungan antara jumlah wajib pajak dan penerimaan pajak untuk pertumbuhan ekonomi Indonesia. Penelitian ini dilakukan pada Kementerian Keuangan Direktorat Jenderal Pajak Republik Indonesia (DJP RI). Direktorat Jenderal Pajak sebagai badan yang memiliki otorisasi dalam regulasi perpajakan diharapkan mampu menegakkan hukum khususnya dibidang perpajakan guna meningkatkan penerimaan negara sebagai bagian dari pertumbuhan ekonomi Indonesia. Kepatuhan wajib pajak terhadap peraturan undang-undang perpajakan diduga mampu meningkatkan pengaruh antara jumlah wajib pajak dan penerimaan pajak untuk pertumbuhan ekonomi. Hipotesis yang disusun dalam penelitian ini adalah: (H1) Jumlah wajib pajak berpengaruh positif terhadap penerimaan pajak; (H2) Teknologi informasi berpengaruh positif terhadap kepuasan wajib pajak; (H3) Kepuasan wajib pajak berpengaruh positif terhadap kepatuhan pajak; (H4) Penegakan hukum berpengaruh positif terhadap kepatuhan pajak; (H5) Kepatuhan pajak berpengaruh positif terhadap pengaruh antara jumlah wajib pajak dengan penerimaan pajak; dan (H6) Penerimaan pajak berpengaruh positif terhadap pertumbuhan ekonomi. Hasil penelitian ini menunjukkan H1, H2, H5 dan H6 terdukung sedangkan H3 dan H4 tidak terdukung. Pengujian terhadap hubungan antar variabel dalam penelitian ini menggunakan data sekunder yang terdapat dalam laporan tahunan Direktorat Jenderal Pajak Republik Indonesia (DJP RI) tahun 2012-2015 dengan menggunakan multiple regression analysis. Data penelitian yang digunakan dalam meliputi data seluruh wajib pajak yang terdapat di seluruh Indonesia, meliputi data wajib pajak orang pribadi, bendahara, dan wajib pajak badan. Kata kunci: jumlah wajib pajak; penerimaan pajak; pertumbuhan ekonomi; kepatuhan wajib pajak